2016
DOI: 10.5194/soil-2-601-2016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term elevation of temperature affects organic N turnover and associated N<sub>2</sub>O emissions in a permanent grassland soil

Abstract: Abstract. Over the last century an increase in mean soil surface temperature has been observed, and it is predicted to increase further in the future. In order to evaluate the legacy effects of increased temperature on both nitrogen (N) transformation rates in the soil and nitrous oxide (N 2 O) emissions, an incubation experiment and modelling approaches were combined. Based on previous observations that gross N transformations in soils are affected by long-term elevated-temperature treatments we hypothesized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…This finding is consistent with previous studies [13,28]. Soil N 2 O production processes primarily involve autotrophic nitrification, heterotrophic nitrification, nitrobacteria denitrification, and chemical denitrification [7][8][9]. Excessive N input and frequent tillage in greenhouse vegetable fields provide substrates and aerobic conditions for ammonia-oxidizing microorganisms [32,33].…”
Section: Relative Importance Of Aoa and Aob In N2o Emissionssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with previous studies [13,28]. Soil N 2 O production processes primarily involve autotrophic nitrification, heterotrophic nitrification, nitrobacteria denitrification, and chemical denitrification [7][8][9]. Excessive N input and frequent tillage in greenhouse vegetable fields provide substrates and aerobic conditions for ammonia-oxidizing microorganisms [32,33].…”
Section: Relative Importance Of Aoa and Aob In N2o Emissionssupporting
confidence: 91%
“…N 2 O is mainly produced after N fertilizer application and by a series of N conversion processes involving autotrophic nitrification, heterotrophic nitrification, nitrobacteria denitrification, chemical denitrification, etc. [7,8]. However, ammonia oxidation, as a necessary step of nitrification, is the main process of N 2 O production in greenhouse vegetable fields [9].…”
Section: Introductionmentioning
confidence: 99%
“…Increased soil temperature may result in lower soil moisture and less N 2 O production as shown for a grassland warming experiment at the GiFACE field site (Jansen-Willems, Lanigan, Clough, Andresen, & M€ uller, 2016), which may counterbalance eCO 2 effects. In contrast, Griffis et al (2017) found a positive correlation between N 2 O emissions and temperature in a 6-year data series from the US corn belt.…”
Section: N 2 O Emissions Under Elevated Comentioning
confidence: 99%